The Problematic Representation of Women: An Analysis of Ratna Indraswari Ibrahim's Literary Text - Moh. Fathoni; Ainul Churria Almalachim (An-Nisa' Journal of Gender Studies, 2022)
Representation of women in literature develops parallelly with the productivity of literary texts. This representation is inevitably intertwined with a discourse that cannot be separated from power relations. Thus, the position and identity of women are vulnerable to domination and subordination. However, women are constructed as subjects and objects, allowing negotiation and contestation to emerge. This article examines the problematic representation of women in Ratna Indraswari Ibrahim's text, "Tina is Just Silent (Tina Diam Saja)," by using Linda Hutcheon's analysis of the female subject in post-modernism discourse. This article reveals that Ibrahim's text produces and reproduces the complicated female subject dealing with power relations. Ibrahim's text provides space for the subject to contest and negotiates her position and identity. "She" offers a silent strategy for the contestation in the text. Therefore, the text allowed female subjects to be problematized by a representation of the consequences of gendered power.